Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Guru SMK Negeri 4 Pekanbaru - Imam Sukarno Putra; Susi Hendriani; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conductedat 4 pekanbaru SMK teachers in order to determine howt he analysis ofthe factors Discipline of Work, Education and Training of the Teacher Performance SMK 4 Pekanbaru. The populationin this study was the teacher of SMK Negeri 4 Pekanbaru. Saturation sampling technique(census) in whichthe entire populationin this study used a sample of 45 teachers. The data obtained were then analyzed descriptively. These results indicate that the factors that affect the performance of teachers of SMK Negeri 4 Pekanbaruis the Discipline of Work, Education and Training. Variable work discipline consisting of indicator adherence to working hours, punctuality in carrying out duties, obedience terjadap leadership, adherence to procedures and methods of work, do the work according to plan and the courage to accept the risk with adequate or poor category (score of 3.37). Education and training variables with indicators selection of the participants, the opportunity to participate, the suitability of educational materials and training of trainers expertise, balance of theory and practice, the effectiveness of the skills, ability to solve problems and balance evaluation of education and training programs with either category (score of 3.90). Variable performance with indicators of learning strategies, facilities, learning difficulties of children, child development evaluation study with either category ( score of 4:09).Keywords: Disciplineof Work, Education and Training and Teacher Performance